Clinical and radiological evaluation of cherubism: a sporadic case report and review of the literature - VAROL, ALTAN; ÖZKAN, YAŞAR (My University, 2003)
Many cases have been published on cherubism since Jones described it first time in three children of the same family [Am. J. Cancer 17 (1933) 946]. Cherubism is an autosomal-dominant disorder in which the normal bone is replaced by cellular fibrous tissue and immature bone. Extracranial skeletal involvement is rarely seen in hereditary and non-hereditary forms of the disorder. The mandible is the most severely affected craniofacial component, in which uncontrolled growth of the malady deteriorates the aesthetic balance of the face. Bilateral swelling of the cheeks, mandibular enlargement and maxillary spongious hypertrophy cause orbital manifestations and tendency of eyes looking up to the sky. Thus, the pathognomic clinical feature resembles the appearance of "raised to heaven" Renaissance cherubs. The sporadic case concerns a child affected by cherubism. Radiographic and clinical data of the patient are presented and brief review of the literature is included.
Keywords: Female; Humans; Tomography, X-Ray Computed; Child; Jaw Abnormalities; Fibrous Dysplasia of Bone; Cherubism